Rituximab in the Treatment of Refractory Myasthenia Gravis: Studying the Outcomes Using MMT Score And Need for Plasmapheresis in Baghdad Teaching Hospital - Abeer Abdulhadi Rashid1, Sarmad Abdulrasool Almashta2, Rana Ali Hussein3, Ahmed khaleel Mashaallah4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Myasthenia gravis (MG) is an uncommon autoimmune disease that is caused by acetylcholine receptor antibodies (AChRA) at the neuromuscular junction. Its pathogenesis involves complement fixing antibodies directed against acetylcholine receptors, muscle-specific tyrosine kinase or low density lipoprotein receptor–related protein. Method: A descriptive case series study investigating rituximab in refractory MG was conducted in Baghdad teaching hospital .Patients who were included in the study had received a regimen of rituximab that was deemed appropriate by their treating physician. Results: A total of 24 patients with mean disease duration of 6.3 years ±3.6 standard deviation were included in this study. The results showed that the average age of patients was 33.3 ,years ±10.1 SD and 62.5% was females. All twenty four patients showed an obvious improvement in clinical status after finishing the follow-up period. The results demonstrated from all patients that enrolled in our study, only one patient that who was on 14 sessions of plasmapheresis was in need for plasmapheresis after induction of rituximab and this difference was statistically significant. Conclusion: There were a great clinical improvement as shown with MMT score in addition to discontinuation of plasma exchange treatments fallowing treatment with rituximab.